İstanbul Süleymaniye bölgesindeki Osmanlı sivil mimarlık örneklerinin,günümüzdeki kullanım ve güncel durumlarının araştırılması - Deniz, Şimşek (My University, 1999)
Suleymaniye neighbourhood, one of the most important historical places of Istanbul which has an important place in the world civilisation history, is from very rare places it reflects present old Istanbul's settlement and residence texture. Suleymaniye neighbourhood I chosen as a subject to my master thesis is an area of 40 hectares in historical Istanbul peninsula. During my thesis study, office activities as to attain knowledge and documents, to combine regularly them, and to move them to computer was realized as synchronical with area study. First section is on the situation of Istanbul and historical peninsula, and historical development process of Suleymaniye neighbourhood. In this section, old maps, which expressed that area, was presented in a chronological line; and the development and change process of suleymaniye was studied. The period from Byzantine to first years of the Republic and actual situation was expressed by accompaniment of the maps in such a scale, photos, graphs and schemes. The structure and functions of the City at the Byzantine period was expressed approximately and schemetically. Conquest and classical period's Suleymaniye was dealt with the Complex and monuments began constructing in its surroundings, and also, Bayazıt II Water Road Map. After the Tanzimat and first period of the Republic were explained by Pervitich Maps which have charasteristic a fire and insurance map. In Second Section, civil architectural samples in Suleymaniye were studied; 255 historical houses's actual situations were established, analysed and classificated. Plan schemes of houses, front orders, used material, kind of carrier, floor numbers and public improvements orders were showed as a criterion. Again, in this section, Suleymaniye houses -they are founded in building island in the Complex's near surroundings- were examined in the base of plot of land; and were gave place to their floor plans, fronts and photos. In addition, the knowledges about the houses were expressed as texts by studing monument cards. In third and also final section, destruction and deterioration process were exposed with its causes; and, in the frame of present establishing and documents, to question what are necessary studies and solvation alternatives to revitalization historical surroundings in this area were looked for an answer.
Keywords: MİMARLIK, İSLAM_TÜRKİYE